CHARACTERISTICS OF SARDINE FISH OIL EMULSION (Sardinella sp.) FLOUR BY-PRODUCT DURING STORAGE - Haryati, Kristina (Jurnal Perikanan Unram, 2025)
Sardine fish oil, which is mostly considered useless, is actually very beneficial because it contains various omega-3 fatty acids, especially EPA and DHA so that fish oil is made into an emulsion product. Emulsion is a two-phase system in which small droplets of one liquid are dispersed into another liquid. The purpose of this study was to determine the characteristics of the best emulsion formula for 30 days of storage. The methods in this study include the stage of determining the emulsion formula, and the emulsion testing stage. In making the emulsion formula, the types of emulsifiers used were Carboxymethyl Cellulose (CMC) and lecithin with a ratio of 1: 1; 1: 2; 3: 1; and 3: 2. The tests carried out included viscosity, pH, and percent stability. The results showed that the highest viscosity, pH, and percent stability tests during 30 days of storage were in formula 3: 1 and the lowest in formula 1: 2. During 30 days of storage, there was a decrease in the viscosity, pH, and emulsion stability values for all formulas. This finding shows that the best emulsion formula uses CMC and lecithin emulsifiers, namely 3:1. Thus, this study shows that sardine fish oil emulsion has the potential to be developed into an emulsion product using the existing formula